The association between computed tomography angiography timing and workflow times in patients with acute ischemic stroke. Issue 5 (July 2021) - Dessens, Femke M; Groot, Adrien E; van der Veen, Bas; Treurniet, Kilian M; Majoie, Charles BLM; Driessen-Waaijer, Annet; Weinstein, Henry C; Roos, Yvo BWEM; Van den Berg-Vos, Renske M; Coutinho, Jonathan M; van Schaik, Sander M
Background: In most hospitals, computed tomography angiography (CTA) is nowadays routinely performed in patients with acute ischemic stroke. However, it is unclear whether CTA is best performed before or after start of intravenous thrombolysis (IVT), since acquisition of CTA before IVT may prolong door-to-needle times, while acquisition after IVT may prolong door-to-groin times in patients undergoing endovascular treatment. Methods: We performed a before-versus-after study (CTA following IVT, period I and CTA prior to IVT, period II), consisting of two periods of one year each. This study is based on a prospective registry of consecutive patients treated with IVT in two collaborating high-volume stroke centers; one primary stroke center and one comprehensive stroke center. The primary outcome was door-to-needle times. Secondary outcomes included door-to-groin times. Quantile regression analyses were performed to evaluate the association between timing of CTA and workflow times, adjusted for prognostic factors. Results: A total of 519 patients received IVT during the study period (246 in period I, 273 in period II). In the adjusted analysis, we found a nonsignificant 1.13 min median difference in door-to-needle times (95% confidence interval: 1.03–3.29). Door-to-groin times was significantly shorter in period II in both unadjusted and adjusted analysis with the latter showing a 19.16 min median difference (95% confidence interval: 3.08–35.24). Conclusions: CTA acquisition prior to start of IVT did not adversely affect door-to-needle times. However, a significantly shorter door-to-groin times was observed in endovascular treatment eligible patients. Performing CTA prior to start of IVT seems the preferred strategy.